Assessing Understanding of Caregivers on Immunization and Covid-19 Vaccines Using: A Survey Instrument - ERCAN, Gozde; Meryem, Özdemir; Sirin, Güven (International Journal of Innovative Research in Medical Science, 2022)
Background: Preventive medicine and immunization are crucial to preserve public health. In this study, it was aimed to determine the perspectives of the caregivers against the immunization services and awareness of the vaccine for the Covid-19 pandemic, which is the most critical challenge in nowadays. Methods: A questionnaire was administered to 205 parents about their knowledge and perceived on immunization and Covid-19 vaccines. Demographic characteristics of families, income and education levels, number of children and presence of Covid-19 vaccination of the parents were sought. Result: Majority of the parents (42%) believe that there are other ways to prevent diseases which can be prevented by a vaccine and 37% of them assume to get not enough information on vaccines. Thirty eight percent of parents presume the vaccine causes the diseases. It was found 70% of the parents assume that not be vaccinated is an individual right. It was observed that as the level of education of the parents increased, the rate of being aware of vaccines and getting them increased. Conclusion: It was concluded that majority of the parents believed that not getting vaccinated is an individual right. A significant number of parents were found to lack information about vaccines. Getting vaccinated is not an individual decision. To increase awareness of caregivers about vaccines can be achieved by providing accurate and appropriate information by health professionals and extended immunization programs to the public.